AEDGE: Atomic experiment for dark matter and gravity exploration in space - Bertoldi, Andrea; Bongs, Kai; Bouyer, Philippe; Buchmueller, Oliver; Canuel, Benjamin; Caramete, Laurentiu-Ioan; Chiofalo, Maria Luisa; Coleman, Jonathon; De Roeck, Albert; Ellis, John; Graham, Peter W.; Haehnelt, Martin G.; et al. (Experimental astronomy, 2021)
This article contains a summary of the White Paper submitted in 2019 to the ESA Voyage 2050 process, which was subsequently published in EPJ Quantum Technology (AEDGE Collaboration et al. EPJ Quant. Technol. 7 ,6 2020 ). We propose in this White Paper a concept for a space experiment using cold atoms to search for ultra-light dark matter, and to detect gravitational waves in the frequency range between the most sensitive ranges of LISA and the terrestrial LIGO/Virgo/KAGRA/INDIGO experiments. This interdisciplinary experiment, called Atomic Experiment for Dark Matter and Gravity Exploration (AEDGE), will also complement other planned searches for dark matter, and exploit synergies with other gravitational wave detectors. We give examples of the extended range of sensitivity to ultra-light dark matter offered by AEDGE, and how its gravitational-wave measurements could explore the assembly of super-massive black holes, first-order phase transitions in the early universe and cosmic strings. AEDGE will be based upon technologies now being developed for terrestrial experiments using cold atoms, and will benefit from the space experience obtained with, e.g., LISA and cold atom experiments in microgravity.